Parallels Between Spain and Germany in the Repression of Primary School Teachers, 1930-1940 - Santiesteban, Andra (Historia y Memoria de la Educación, 2025)
The repression exerted on primary school teachers between 1930 and 1940, in the context of the rise of fascism in Europe, represented an educational event of transnational significance. Since the 1990s, historiographical studies in both Spain and Germany have sought to reconstruct the memory of the teaching profession and brought to light the silences imposed by Francoism and Nazism. From the perspective of the History of Education, it has been revealed how the hegemonic narrative regarding the repressive and purging processes served the political agendas of both regimes. In both Madrid (1939-1975) and Berlin (1933-1945), teachers underwent an ideological purge aimed at politically and socially controlling this group of civil servants. This was done by removing from service those teachers who were Jewish, «non-Aryan», political dissidents, as well as Freemasons, «anti-religious», or «anti-patriotic» individuals. In our research, we examined the lustration implemented in both regions, seeking to identify parallels in their approaches and effects from a comparative approach. For this purpose, the historical-educational method was used, based on the analysis of primary sources, such as service sheets, administrative reports and depuration files. In addition, these documents were triangulated with official bulletins and other historical sources. Regarding the object of study, the research provided results not only in quantitative and qualitative terms but also contributed to orienting the present towards a critical pedagogy. By uncovering the similarities and differences in the repression of teachers in Madrid and Berlin, a deeper and more comprehensive understanding of school memory in the European context and in a transnational key was fostered.